Discovering novel reproductive genes in a non-model fly using de novo GridION transcriptomics - Walter, Mrinalini; Puniamoorthy, Nalini (Frontiers in Genetics, 2022)
Gene discovery has important implications for investigating phenotypic trait evolution, adaptation, and speciation. Male reproductive tissues, such as accessory glands (AGs), are hotspots for recruitment of novel genes that diverge rapidly even among closely related species/populations. These genes synthesize seminal fluid proteins that often affect post-copulatory sexual selection – they can mediate male-male sperm competition, ejaculate-female interactions that modify female remating and even influence reproductive incompatibilities among diverging species/populations. Although de novo transcriptomics has facilitated gene discovery in non-model organisms, reproductive gene discovery is still challenging without a reference database as they are often novel and bear no homology to known proteins. Here, we use reference-free GridION long-read transcriptomics, from Oxford Nanopore Technologies (ONT), to discover novel AG genes and characterize their expression in the widespread dung fly, Sepsis punctum. Despite stark population differences in male reproductive traits (e.g.: body size, testes size, sperm length) as well as female re-mating, the male AG genes and their secretions of S. punctum are still unknown. We implement a de novo ONT transcriptome pipeline incorporating quality-filtering and rigorous error-correction procedures, and we evaluate gene sequence and gene expression results against high-quality Illumina short-read data. We discover highly-expressed reproductive genes in AG transcriptomes of S. punctum consisting of 40 high-quality and high-confidence ONT genes that cross-verify against Illumina genes, among which 26 are novel and specific to S. punctum. Novel genes account for an average of 81% of total gene expression and may be functionally relevant in seminal fluid protein production. For instance, 80% percentage of genes encoding secretory proteins account for 74% total gene expression. In addition, median sequence similarities of ONT nucleotide and protein sequences match within-Illumina sequence similarities. Read-count based expression quantification in ONT is congruent with Illumina’s Transcript per Million (TPM), both in overall pattern and within functional categories. Rapid genomic innovation followed by recruitment of de novo genes for high expression in S. punctum AG tissue, a pattern observed in other insects, could be a likely mechanism of evolution of these genes. The study also demonstrates the feasibility of adapting ONT transcriptomics for gene discovery in non-model systems.